2021
DOI: 10.1186/s42779-021-00105-4
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Sri Lankan fermented buffalo (Bubalus bubalis) milk gel (Meekiri): technology, microbiology and quality characteristics

Abstract: Meekiri (sometimes also known as Mee-Deekiri); fermented buffalo milk gel is a deep-rooted dairy product in Sri Lankan food culture and the production of Meekiri plays an integral part in the livelihood of rural farming. Meekiri consumption is widespread irrespective of geographic boundaries, across the cultural and/or ethnic communities. In Sri Lanka, buffalo milk is predominantly used in producing Meekiri, where production has been specialized in various geographic areas in the country, associated with major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…It is preferred because it absorbs the excess of whey and allows specific sensory properties, mainly in terms of flavor and texture. Moreover, clay pots are characterized as permeable materials to moisture and gases, and do not react with foods compared to plastic containers which are still used in many countries [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is preferred because it absorbs the excess of whey and allows specific sensory properties, mainly in terms of flavor and texture. Moreover, clay pots are characterized as permeable materials to moisture and gases, and do not react with foods compared to plastic containers which are still used in many countries [31].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the effect of fermentation vessels on the variation of apparent viscosity and color parameters of fermented goat milk. A study conducted by Priyashantha et al [31] on Meekiri, a traditional dairy product made in clay pot, showed that the fermented milk was characterized by a high viscosity and creamy and thick mouthfeel attributes. Moonga et al [11] for Mabisi also reported similar results, describing that higher viscosity was also correlated to the fermenting bacteria consortia [33].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported increased levels of syneresis (a 12% increase in syneresis compared to d-1 of the refrigerated storage) for buffalo milk yoghurt after 21 d of refrigerated storage when stored in plastic cups (Yapa et al, 2023). The clay pots were reported to absorb excess whey from the curd matrix to maintain the textural properties of curd (Priyashantha et al, 2021). Therefore, obtaining decreasing levels of syneresis over the storage in our study may be due to the use of clay pots that may absorb expulsing whey from the curd matrix.…”
Section: Syneresismentioning
confidence: 99%
“…Traditionally, the source of starter culture is called "muhum" (in Sinhalese), which is a small portion of previously prepared curd (half to one day old). This method is called back-sloping (Siriweera, 2009;Priyashantha et al, 2021). The temperature of the milk when the muhum was added is determined by experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation